A conditional mutant of the fatty acid synthase unveils unexpected cross talks in mycobacterial lipid metabolism. Issue 2 (22nd February 2017) - Cabruja, Matías; Mondino, Sonia; Tsai, Yi Ting; Lara, Julia; Gramajo, Hugo; Gago, Gabriela
Abstract : Abstract : Unlike most bacteria, mycobacteria rely on the multi-domain enzyme eukaryote-like fatty acid synthase I (FAS I) to make fatty acids de novo. These metabolites are precursors of the biosynthesis of most of the lipids present both in the complex mycobacteria cell wall and in the storage lipids inside the cell. In order to study the role of the type I FAS system in Mycobacterium lipid metabolism in vivo, we constructed a conditional mutant in the fas-acpS operon of Mycobacterium smegmatis and analysed in detail the impact of reduced de novo fatty acid biosynthesis on the global architecture of the cell envelope. As expected, the mutant exhibited growth defect in the non-permissive condition that correlated well with the lower expression of fas-acpS and the concomitant reduction of FAS I, confirming that FAS I is essential for survival. The reduction observed in FAS I provoked an accumulation of its substrates, acetyl-CoA and malonyl-CoA, and a strong reduction of C12 to C18 acyl-CoAs, but not of long-chain acyl-CoAs (C19 to C24 ). The most intriguing result was the ability of the mutant to keep synthesizing mycolic acids when fatty acid biosynthesis was impaired. A detailed comparative lipidomic analysis showed that although reduced FAS I levels had a strong impact on fatty acid and phospholipid biosynthesis, mycolic acids were still being synthesized in the mutant, although with a different relative species distribution. However, when triacylglycerol degradation was inhibited, mycolic acid biosynthesis was significantly reduced, suggesting that storage lipids could be an intracellular reservoir of fatty acids for the biosynthesis of complex lipids in mycobacteria. Understanding the interaction between FAS I and the metabolic pathways that rely on FAS I products is a key step to better understand how lipid homeostasis is regulated in this microorganism and how this regulation could play a role during infection in pathogenic mycobacteria.